Repellent properties of Pithecellobium dulce (Roxb.) Benth. (Family: Fabaceae) against fi lariasis vector, Culex quinquefasciatus Say (Diptera: Culicidae) - M. Rajeswary, M. Govindarajan (Journal of Medicinal Herbs and Ethnomedicine, 2015)
To determine the repellent activity of hexane, ethyl acetate, benzene, chloroform, and methanol extract of Pithecellobium dulce leaf and seed against filariasis vector, Culex quinquefasciatus. Evaluation was carried out in a net cage (45 cm2 Ã— 30 cm2 Ã— 25 cm2) containing 100 blood starved female mosquitoes of three mosquito species and were assayed in the laboratory condition by using the protocol of WHO: The plant leaf crude extracts of P. dulce was applied at 1.0, 2.5, and 5.0 mg/cm2 separately in the exposed area of the fore arm. Only ethanol served as control. In this observation, the plant crude extracts gave protection against mosquito bites without any allergic reaction to the test person, and also, the repellent activity is dependent on the strength of the plant extracts. Among the tested solvents, both the leaf and seed methanol extracts showed maximum efficacy. The highest concentration of 5.0 mg/cm2 provided over 120 min and 90 min protection for the leaf and seed extracts, respectively. From the results, it can be concluded the crude extract of P. dulce was potential for controlling filariasis vector, C. quinquefasciatus mosquito.